Statistical analysis in simple steps using R - Pandya, Kiran (Sage, 2018)
An open and dynamic software for statistical analysis, R has become increasingly popular among students and researchers alike for its powerful language and graphical abilities. This book incorporates a step-by-step approach to the basics of statistical tests, the prerequisites and assumptions, the procedures, and outputs and their interpretation all through the lens of R. It is a concise guide to procuring and using R, identifying the types of tests to examine different types of research questions, and the sequential steps for undertaking statistical analysis. Intended largely for readers who are new to statistics or R or to both, this textbook addresses the problems in statistical analysis often faced by the students of social science, education, and management.